Analysis of Food System Topics from the Consumers’ Perspective in a Developing Country Context: Key Insights from ANRS Metropolitan Cities, Ethiopia - Mengesha ST (Dove Medical Press, 2021)
Seyoum Teffera Mengesha Department of Economics, College of Business and Economics, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Seyoum Teffera MengeshaDepartment of Economics, College of Business and Economics, Bahir Dar University, PO Box: 618, Addis Alem, Bahir Dar, EthiopiaTel +251 910194677Email seyoumteffera@gmail.com; Seyoum.Teffera@bdu.edu.etBackground: The food system is an interdisciplinary global issue with substantial social and economic challenges. These challenges are most pronounced in developing countries, where chronic under-nutrition is prevalent. The long-standing notion has been to solve malnutrition and undernutrition primarily from the supply side through improving productivity and production. Nevertheless, addressing the nutrition paradox requires understanding consumers' food choices and its drivers.Methods: This study forms a part of a research project conducted in the ANRS, Ethiopia, in both urban and rural settings. To select study participants and collect data from the ANRS metropolitan cities, we used a household-based cross-sectional study and a multistage sampling technique. Data were collected using a structured questionnaire, and the study used a descriptive research method and a quantitative research approach in its analysis. PCA was used to identify which topics in the food system are most important to consumers.Results: To identify widely held consumer interests, respondents were asked to report their interest in several relevant topics. The results show that food systems' external impact, food safety, food nutrition, impact of other bodies on the food system, and food supply sustainability are the most crucial food topics where consumers are interested.Conclusion: Concerned stakeholders who can help enhance household dietary practices in the study area; producers and other stakeholders who care about environmental sustainability and/or social values might use this information to adjust their production and marketing decisions to align with the food system topics that consumers identified as their priority.Limitations: While the PCA allows for the reduction of multiple indices into a single composite index, it may restrict the targeting of a particular aspect of the food system topic. As a result, the indices' meaning, and implications should be made while keeping the downsides in mind.Keywords: food system topic, consumers, nutrition, Ethiopia